Shifts to earlier selfing in sympatry may reduce costs of pollinator sharing. (1st August 2018) - Randle, April M.; Spigler, Rachel B.; Kalisz, Susan
Abstract: Coexisting plant congeners often experience strong competition for resources. Competition for pollinators can result in direct fitness costs via reduced seed set or indirect costs via heterospecific pollen transfer (HPT), causing subsequent gamete loss and unfit hybrid offspring production. Autonomous selfing may alleviate these costs, but to preempt HPT, selfing should occur early, before opportunities for HPT occur (i.e., "preemptive selfing hypothesis"). We evaluated conditions for this hypothesis in Collinsia sister species, C. linearis and C. rattanii . In field studies, we found virtually identical flowering times and pollinator sharing between congeners in sympatric populations. Compared to allopatric populations, sympatric C. linearis populations enjoyed higher pollinator visitation rates, whereas visitation to C. rattanii did not differ in sympatry. Importantly, the risk of HPT to each species in sympatry was strongly asymmetrical; interspecies visits comprised 40% of all flower‐to‐flower visits involving C. rattanii compared to just 4% involving C. linearis . Additionally, our greenhouse experiment demonstrated a strong cost of hybridization when C. rattanii was the pollen donor. Together, these results suggest that C. rattanii pays the greatest cost of pollinator sharing. Matching predictions of the preemptive selfing hypothesis, C. rattanii exhibit significantly earlier selfing in sympatric relative to allopatric populations.